Sistem Aplikasi Point of Sale berbasis Desktop pada Qini Mart Tasikmalaya - Yanti Apriyani; Mira Kusmira; Iqbal Dzulfiqar Iskandar; Imam Amirulloh; Melisa Winda Pertiwi; Taufik Wibisono (Universitas Hamzanwadi, 2022)
Public interest in the modern market has increased rapidly, resulting in market business actors having difficulty in handling a large number of transactions as experienced by one of the market business players, namely Qini Mart Tasikmalaya. This study aims to create a Point of Sales (POS) application program in market businesses that can handle good retail management processes. In this study, we used a spiral model to build or design a POS application at Qini Mart Tasikmalaya. In this model, there is a risk analysis that is useful arising from the needs and designs that have been made in previous stages so that they can adjust, simplify, and speed up the retail management process. Black-box testing is used to determine the level of functionality and interface of the system that we have developed. The findings resulted in a POS application used at Qini Mart Tasikmalaya in accordance with the design we have made. In addition, the results of black-box testing show that all functional and interfaces on the system are running well, where this system can speed up the process of calculating sales transactions, printing payment notes, facilitating the process of managing goods data, and making more accurate sales reports.